A new approach to raising social security's earliest eligibility age - Kelly Haverstick; Margarita Sapozhnikov; Robert K. Triest; Natalia Zhivan (Federal Reserve Bank of Boston, 2008)
While Social Securityfs Normal Retirement Age (NRA) is increasing to 67, the Earliest Eligibility Age (EEA) remains at 62. Similar plans to increase the EEA raise concerns that they would create excessive hardship on workers who are worn]out or in bad health. One simple rule to increase the EEA is to tie an increase to the number of quarters of covered earnings. Such a provision would allow those with long work lives.presumably the less educated and lower paid.to quit earlier. We provide evidence that this simple rule would not satisfy the goal of preventing undue hardship on certain workers. Therefore, this paper considers an alternative policy that ties an increase in the EEA to individualsf Average Indexed Monthly Earnings (AIME). We show that allowing workers with low AIME to continue to be eligible to receive benefits at age 62 has promise as a policy to protect workers who have low earnings and are in poor health from hardship associated with an increase in the EEA.
Keywords: H55; J26; I12; 330